2007
DOI: 10.2332/allergolint.r-07-153
|View full text |Cite
|
Sign up to set email alerts
|

Airway Remodeling in Asthma

Abstract: Airway remodeling can be defined as changes in the composition, content, and organization of the cellular and molecular constituents of the airway wall. Airway remodeling is a characteristic feature of asthma, and has important functional implications. These structural changes include epithelial detachment, subepithelial fibrosis, increased airway smooth muscle (ASM) mass, decreased distance between epithelium and ASM cells, goblet cell hyperplasia, mucus gland hyperplasia, proliferation of blood vessels and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
121
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 64 publications
1
121
0
5
Order By: Relevance
“…All these modifications thicken airway walls in asthmatic patients, leading to airway hyperresponsiveness to specific allergens and non-specific stimuli (9). Thus, the existence of airway remodeling may be closely associated with antigen-induced airway narrowing, including LAR (9,10); however, the relationship between antigen-induced airway narrowing and airway remodeling has not been examined, even in experimental animals. Furthermore, studies using murine models have shown that airway remodeling was also mediated by activation of CD4 + cells because anti-CD4 mAb effectively suppressed the histological changes (11); however, another study demonstrated that CD4 + cells were not required for progressive airway remodeling (12).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…All these modifications thicken airway walls in asthmatic patients, leading to airway hyperresponsiveness to specific allergens and non-specific stimuli (9). Thus, the existence of airway remodeling may be closely associated with antigen-induced airway narrowing, including LAR (9,10); however, the relationship between antigen-induced airway narrowing and airway remodeling has not been examined, even in experimental animals. Furthermore, studies using murine models have shown that airway remodeling was also mediated by activation of CD4 + cells because anti-CD4 mAb effectively suppressed the histological changes (11); however, another study demonstrated that CD4 + cells were not required for progressive airway remodeling (12).…”
Section: Introductionmentioning
confidence: 97%
“…These changes include fibroblast proliferation, airway smooth muscle hyperplasia and hypertrophy, and excess production of mucus (9,10). All these modifications thicken airway walls in asthmatic patients, leading to airway hyperresponsiveness to specific allergens and non-specific stimuli (9).…”
Section: Introductionmentioning
confidence: 99%
“…A defining histopathological feature of the respiratory tissues amongst asthmatics is the increased infiltration of leukocytes, predominantly eosinophils and allergen-specific CD4+ Th2 cells (Nauta et al;Warner & Knight, 2008;Kay, 1988;Sumi & Hamid, 2007;Lloyd & Rankin, 2003;D'Ambrosio et al, 2003;Gwinn et al, 2006;Kelly et al, 2007). The entire stomach mucosa during asthma, as in the respiratory tissues, has been noted to show an increased influx of lymphocytes; however, no studies to date have determined if these invading lymphocytes are allergen-specific CD4+ Th2 cells (Nepomnyashchikh et al).…”
Section: Introductionmentioning
confidence: 99%
“…3 Air way re mo de ling is prog res si ve struc tu ral chan ges in the com po si ti on, con tent, and or ga niza ti on of the cel lu lar and mo le cu lar cons ti tu ents of the air way wall. 4 Alt ho ugh cur rent ast hma the rapi es are ef fec ti ve in re du cing inf lam ma ti on, air way re mo de ling is po orly res pon si ve to cur rent the rapi es, such as in ha led cor ti cos te ro ids, an ti le u kot ri enes, and the ophy lli ne. 4,5 Thus, new the ra pe u tic op ti ons are re qu i red.…”
mentioning
confidence: 99%
“…4 Alt ho ugh cur rent ast hma the rapi es are ef fec ti ve in re du cing inf lam ma ti on, air way re mo de ling is po orly res pon si ve to cur rent the rapi es, such as in ha led cor ti cos te ro ids, an ti le u kot ri enes, and the ophy lli ne. 4,5 Thus, new the ra pe u tic op ti ons are re qu i red.…”
mentioning
confidence: 99%